2018
DOI: 10.15294/higeia.v2i2.19388
|View full text |Cite
|
Sign up to set email alerts
|

Kejadian Tuberkulosis Multi Drug Resistant di RSUP dr. Kariadi

Abstract: Indonesia ranks 8th out of 27 countries with high priority burden of MDR TB. MDR Tuberculosis at Dr. Kariadi has increased over the last 3 years. In 2014 there were 688 cases, 2015 there were 1,183 cases, 2014 reached 1442 cases, until May 2017 reached 2,061 cases. The purpose of this study was to analyze factors related to MDR TB incidence at RSUP. Dr. Kariadi Kota Semarang. This research was analytic observational case control design. The samples were 72 cases and 72 controls by purposive sampling technique.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
1
0
2
Order By: Relevance
“…Current study showed the most dominant determinants of drug-resistant PTB were the history of previous treatment and AFB gradation. These findings consistent and similarly with previous studies [11][12][13][14], while the recent study in Dr. Kariadi General Hospital showed that previous treatment was not the determinant of drug-resistant PTB [9]. The current study confirmed well-known common knowledge of the determinants for drug-resistant PTB.…”
Section: And Figsupporting
confidence: 93%
See 1 more Smart Citation
“…Current study showed the most dominant determinants of drug-resistant PTB were the history of previous treatment and AFB gradation. These findings consistent and similarly with previous studies [11][12][13][14], while the recent study in Dr. Kariadi General Hospital showed that previous treatment was not the determinant of drug-resistant PTB [9]. The current study confirmed well-known common knowledge of the determinants for drug-resistant PTB.…”
Section: And Figsupporting
confidence: 93%
“…This finding also have been proved by previous study in Dr. Kariadi General Hospital as the most dominat factor that related to the MDR-TB cases. Patients with duration of treatment more than 7 months had 3.23 times higher risk to be resistant [9]. Based on bivariate analysis, current study also concluded that patients with duration of treatment more than 6 months would have 6.9 times higher risk to get drug-resistant PTB case as shown in Table II.…”
Section: And Figmentioning
confidence: 50%
“…Riwayat pengobatan TB sebelumnya paling dominan berhubungan dengan kejadian MDR. Riwayat pengobatan TB gagal dan putus berobat merupakan faktor terjadinya TB MDR 5 . Hal yang sama juga dibuktikan dengan penelitian lain yaitu riwayat pengobatan TB berhubungan dengan kejadian MDR TB 6 .…”
Section: Pendahuluanunclassified
“…Penelitian Triandari menyatakan terdapat hubungan antara pendapatan seseorang dengan kejadian MDR-TB. 28 Pendapatan yang rendah berisiko 3 kali untuk menjadi MDR-TB. 29 Seseorang dengan pendapatan rendah akan sulit untuk memenuhi kebutuhan gizi keluarganya sehingga akan berdampak terhadap kesehatannya.…”
Section: Pembahasan Karakteristik Subjek Penelitianunclassified